Labor productivity and vocational training: evidence from Europe - Sala, Hector; Silva, José I. (Bonn, 2011)
"In this paper we show that vocational training is an important determinant of productivity growth. We construct a multi-country, multi-sectoral dataset, and quantify empirically to what extent vocational training has contributed to increase the growth rate of labor productivity in Europe between 1999 and 2005. We find that one extra hour of training per employee accelerates the rate of productivity growth by around 0.55 percentage points."